Co-composting of poultry manure with other agricultural wastes: process performance and compost horticultural use - Rizzo, Pedro Federico; Della Torre, Virginia; Riera, Nicolas; Crespo, Diana Elvira; Barrena, Raquel; Sánchez, Antoni (2018)
The aim of this work was to evaluate the composting process of poultry manure mixed with other complementary organic wastes. Two mixtures (treatment 1 and 2) were prepared with corn bare cobs, sawdust, shavings and manure. Temperature, pH, electrical conductivity, organic matter loss, total organic carbon, solved organic carbon, N loss, ammonium and nitrate concentration, laccase activity and respiration indices were analyzed. These variables showed similar tendencies during the composting process in both treatments. A peak of biological activity, organic matter mineralization and salt release was observed after 6 days of the process. Treatment 2 showed a higher concentration of solved organic carbon and higher organic matter loss than in the mixture with less manure (treatment 1). Laccase activity increased when solved organic carbon decreased. Compost from treatment 1 showed lower phytotoxic effects than that from treatment 2, probably because of a low salt content. In conclusion, it was observed that 60 % content of poultry manure in the mixture does not affect the composting process. However, the final product is not as good for agricultural purposes as a mixture with a lower manure content. Finally, it can be stated that the valorization of these wastes in the form of compost adds value to the materials, closing the biogeochemical nutrient cycle.